Replication catastrophe induced by cyclic hypoxia leads to increased APOBEC3B activity - Bader, SB (2020)
Regions of low oxygen (hypoxia) occur in most human solid tumours and correlate with a poor patient prognosis as hypoxic regions are resistant to most cancer therapies and have an increased metastatic potential. Hypoxia is a highly dynamic state, characterised by oxygen fluctuations on the order of minutes, hours, and days occurring simultaneously in regions throughout the tumour. Dynamic changes in tumour oxygenation are referred to as “cyclic hypoxia” that can span a wide range of oxygen tensions. Cells that experience severe levels of hypoxia (<0.1% O2) are characterised by replication stress and the activation of the DNA damage response, in the absence of DNA damage. The apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like (APOBEC) proteins are a family of eleven conserved cytidine deaminases that play a critical role in viral immunity through the deamination of viral transcripts. APOBECs have been shown to be responsible for the generation of mutational signatures in human cancers through their capability to deaminate cytosine bases to uracil in genomic DNA. How these mutational signatures arise in human cancer is currently unknown. Recently it was shown that hydroxyurea induced replication stress resulted in an up regulation of APOBEC3B and an increase in cellular deamination in vitro. This finding led us to ask if APOBEC activity would be increased in response to the physiologically relevant stress of hypoxia, which also induces replication stress. In contrast to our original hypothesis, we show that in response to chronic hypoxia (<0.1% O2), the expression of APOBEC3B and APOBEC mediated deamination decreased. However, in response to cyclic hypoxia, APOBEC3B expression and activity increased. Most importantly, APOBEC3B induction in cyclic hypoxia was found to be dependent on replication catastrophe as opposed to replication stress. Furthermore, we provide evidence of hypoxia-dependent regulation of APOBEC-mediated activity in patient tumours. Specifically, a positive correlation can be seen between hypoxia and both the number of APOBEC mutations and the expression of A3B in human tumour samples. These data suggest that replication catastrophe induced by cyclic hypoxia is a plausible mechanism for the generation of the APOBEC mutation signatures in human cancer.